Interaction of inflammatory parameters and thiol/disulfide system of antioxidant protection in chronic obstructive pulmonary disease - Tatyana I. Vitkina; Elena E. Mineeva; Karolina A. Sidletskaya (Russian Open Medical Journal)
Introduction — Increased incidence and prevalence of chronic obstructive pulmonary disease (COPD) provides rationale for describing the disease progression mechanism, considering the interaction of key participants of this process. The objective of our study was to establish the dysfunction parameters of thiol/disulfide system components and adaptive immunity unit in patients with stable chronic obstructive pulmonary disease (COPD). Material and Methods — We examined patients with stable COPD of moderate (62 subjects) or severe (50 subjects) grades. The control group included 32 subjects. Prooxidant and antioxidant markers of oxidative stress were investigated with ELISA. We determined cytokine levels in blood plasma and the number of T helper cells expressing IL-6R with flow cytometry (BD FACSCanto II, USA). Correlation pleiads sensu Terentiev were employed to visualize the data. Results — Changes in both antioxidant and cytokine status of subjects with COPD of varying severity grades implied the progression of systemic inflammation in conditions of uncontrolled activation of adaptive immunity unit rather than just a shift in the peroxide balance and an increase in oxygen metabolites. Conclusion — Accumulation of biomolecule peroxidation products, imbalance in the prooxidant-antioxidant system, and a change in pathogenetic mechanism of inflammation could lead to an aggravated course of bronchopulmonary pathology.